К проблематике способов глагольного действия в русской и литовской аспектологии - Галнайтите, Э. (Kalbotyra, 1980)
Despite the fact that the problem of Aktionsart has been subjected to a thorough analysis the principles underlying the whole system are still open to question. Aktionsarten are either differentiated on the basis of the semantics of verbs, taking into account their morphological characteristics as well, or they are considered to be structural-semantic groups of verbs distinguished by their morphemic features. More often than not (in Lithuanian aspectology in particular) Aktionsarten are confused with other semantic groups, e. g. terminative – non-terminative verbs. Summing up the observations concerning tbe nature of Aktionsart the author arrives at the conclusion that the interpretation of Aktionsart in terms of the semantics of verbs is more convincing.